Human Urogenital Myiasis Caused by Lucilia sericata (Diptera: Calliphoridae) and Wohlfahrtia magnifica (Diptera: Sarcophagidae) in Markazi Province of Iran - Salimi, M (Tehran University of Medical Sciences, 2010)
We report a case of human urogenital myiasis in an 86-year-old rural man with a penil ulcer and numerous alive and motile larvae from urethra and glans penis. Entomological studies on adult flies showed the larvae were Lucilia sericata and Wohlfahrtia magnifica. The clinical presentation and treatment strategies are discussed.